2016
DOI: 10.1177/2165143416629629
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gender on Non-Academic Skills Associated With Post-School Employment and Further Education

Abstract: Gender differences have been found in post-school outcomes of students with disabilities, yet these differences are rarely examined. To determine whether male and female high school students with disabilities scored differently in non-academic behaviors known to affect post-school education and employment measured by the Transition Assessment and Goal Generator, we analyzed scores provided by 1,537 high school students with disabilities, 836 family members, and 139 professionals from 30 states. Findings reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Findings from the two correlational studies included skills correlated to positive postschool outcomes for students with disabilities, which were promoted by teachers (Pham, 2013), as well as weak relationship between nonacademic behaviors associated with postschool education and employment measured by the Transition Assessment and Goal Generator (TAGG;McConnell, Martin, & Hennessey, 2015). Findings from the causal comparative study indicated no differences in scores on professional or student versions of the TAGG based on gender of the student, however, family member's scores were higher for females and differences were found at the construct level on all three versions (McConnell, Martin, Herron, & Hennessey, 2017). Finally, the literature review identified 10 nonacademic constructs and behaviors (e.g., goal setting and attainment, disability awareness, self-advocacy) associated with positive postschool outcomes of students with mild to moderate disabilities (McConnell et al, 2013).…”
Section: Measurementmentioning
confidence: 99%
“…Findings from the two correlational studies included skills correlated to positive postschool outcomes for students with disabilities, which were promoted by teachers (Pham, 2013), as well as weak relationship between nonacademic behaviors associated with postschool education and employment measured by the Transition Assessment and Goal Generator (TAGG;McConnell, Martin, & Hennessey, 2015). Findings from the causal comparative study indicated no differences in scores on professional or student versions of the TAGG based on gender of the student, however, family member's scores were higher for females and differences were found at the construct level on all three versions (McConnell, Martin, Herron, & Hennessey, 2017). Finally, the literature review identified 10 nonacademic constructs and behaviors (e.g., goal setting and attainment, disability awareness, self-advocacy) associated with positive postschool outcomes of students with mild to moderate disabilities (McConnell et al, 2013).…”
Section: Measurementmentioning
confidence: 99%
“…Student grade point average (GPA) and percent of time students received instruction in general education had no meaningful effect on TAGG scores (McConnell, Martin, & Hennessey, 2015). Last, students’ gender had no overall effect on TAGG results, but gender did impact a couple constructs, including employment, likely because males had more employment experiences than females (McConnell, Martin, Herron, & Hennessey, 2016).…”
mentioning
confidence: 96%